A sustainable biogas model in China: The case study of Beijing Deqingyuan biogas project. (October 2017) - Chen, Lihong; Cong, Rong-Gang; Shu, Bangrong; Mi, Zhi-Fu
Abstract: According to the Paris Agreement, China has the ambition to develop non-fossil energy which will account for 20% of the total energy consumption in 2030. China has abundant biomass potential implying the bioenergy should be an important option of non-fossil energy. In this analysis, we present an representative biogas project (the Deqingyuan project, DQY) in Beijing and conduct a cost-benefit analysis for the whole value chain. DQY is the first large-scale biogas project in China that utilizes 100% chicken manure as a feedstock and integrates biogas production with ecological agriculture using advanced technologies. DQY uses 80, 000 t of chicken manure and 100, 000 t of sewage each year to produce biogas, which generates 14 million KWh of power annually, and obtains an additional revenue of RMB 8 million yuan each year through the Clean Development Mechanism (CDM). Operating as an example of a sustainable bioenergy model, DQY accomplishes the full use of a recycled resource while showing consideration for animal welfare during the entire production, which is a fundamental component of the new rural energy strategy. The circular economy model of DQY plays a prominent role in reducing greenhouse gas emissions, mitigating pollution, and increasing employment, among other benefits. This paper aims to conduct a comprehensive analysis of the typical demonstration model (DQY) in utilization of agricultural waste in China, and further proposes a general development model of Chinese biogas in the future.